Delayed School Starts for Middle and High Schools Makes Sense. Issue 5 (September 2018) - Beal, Judy A.
Abstract : Beginning the school day a bit later than traditional start times has been found to have numerous benefits for adolescents because it allows them to get more sleep. While there are barriers to making this happen, a number of school districts in 45 states have been able to change start times. Our pediatric nursing expert, Dr. Beal, describes the risks of sleep deprivation for teens, benefits of adequate sleep, and recent recommendations from the American Academy of Pediatrics and the American Academy of Sleep Medicine.